2016
DOI: 10.21082/ijas.v4n2.2003.p56-62
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Seedling Establishment of Wet Seeded Rice Using Ga3 and Iba as Seed Treatment

Abstract: Direct seeding has some advantages compared to transplanting system in rice, however there are some constraints need to be addressed. One  constraint generally faced in the wet seeded rice is poor stand  establishment. The experiment was conducted to improve seedling  establishment by using selected growth regulators. Seeds of four rice  cultivars, i.e. Memberamo, Widas, MR 84, and MR 219 were treated with  GA3 (gibberellic acid-3) of 25, 50, and 100 mg 1-1, and IBA (indole-3  butyric acid) of 10, 20, and 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
(5 reference statements)
1
0
1
Order By: Relevance
“…The reason may be due to that the priming with gibberellin enhanced the endogenous gibberellin, which led to the accumulation of mRNA nucleic acids. Then, the formation of glucose from the digestion of starch by synthesizing the degradation enzymes Alpha-amylase, which improves the synthesis of sucrose used for growth, this effect is reflected on plumule, as gibberellin contributes to activating the processes of division and elongation (Wahyuni et al, 2016). This result agreed with (Saudi, 2012;Jiyad, 2008;Jadoua and Silawi 2012) indicated that the gibberellin increased the plumule length for the sunflower, sorghum, and rice seedling.…”
Section: Plumule Length In a Standard Laboratory Germination Test (Cm)supporting
confidence: 70%
“…The reason may be due to that the priming with gibberellin enhanced the endogenous gibberellin, which led to the accumulation of mRNA nucleic acids. Then, the formation of glucose from the digestion of starch by synthesizing the degradation enzymes Alpha-amylase, which improves the synthesis of sucrose used for growth, this effect is reflected on plumule, as gibberellin contributes to activating the processes of division and elongation (Wahyuni et al, 2016). This result agreed with (Saudi, 2012;Jiyad, 2008;Jadoua and Silawi 2012) indicated that the gibberellin increased the plumule length for the sunflower, sorghum, and rice seedling.…”
Section: Plumule Length In a Standard Laboratory Germination Test (Cm)supporting
confidence: 70%
“…In the mentioned study, salicylic acid at 150 mg L -1 was introduced to be used as hormonal priming for higher productivity of MR219 rice in Malaysia (Kareem et al, 2013). In contrast to the above results, Wahyuni et al (2013) reported that different responses of MR219 and MR84 rice varieties to various priming treatments depended on several factors such as sowing time, interaction between plant growth regulator and variety, as well as priming stages. In another study, cowpea seed treated with 5 mg L -1 G 3 A 3 and IAA displayed a significant increase in seedling growth and germination percentage cowpea.…”
Section: Hormonal Primingcontrasting
confidence: 69%